(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2025)
This research comparatively examined the use of temporary case notes at the Federal medical Centre (FMC) and the Niger Delta University Teaching hospital (NDUTH) in Yenagoa, Bayelsa State,Nigeria. The objective of the study was to among others, ascertain the cause(s) for creating temporary case notes and its purpose as well as the challenges bedevilling its use by medical professionals in hospitals. The study followed a survey research design in the collection of primary data from 185 healthcare professionals in the two medical hospitals. Moreover, frequencies, percentages and mean scores were used in the analysis of the data. The findings shows’ that the respondents asserted that mislaying and misfiling of patient’s original health records and the over-dependence on a manual system that is burdensome are often the catalyst of temporary case notes in hospitals. The findings also suggests that the purpose of deploying temporary case notes in most hospitals is to ensure a process that facilitates patient’s access to healthcare services devoid of any impediments. The study however observed that respondents view the use of temporary case notes as not equivalent to the original medical record and therefore a challenge to qualitative healthcare service delivery. The research therefore recommends that a comprehensive health records management policy should be formulated to safeguard private medical records of patients and outline the conditions that guide the retrieval and use of medical records by public and private entities in the country. In addition, manual record systems should be overhauled with the introduction of electronic health record management systems to ensure efficiency.